2018
DOI: 10.1186/s12917-018-1463-7
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory mechanism of Rumenitis in dairy cows with subacute ruminal acidosis

Abstract: BackgroundSubacute ruminal acidosis (SARA) is a metabolic disease in high-producing dairy cattle, and is accompanied by rumenitis. However, the mechanism of rumenitis remains unclear. Therefore, the aim of this study was to investigate the molecular mechanism of rumenitis in dairy cows with SARA.ResultsThe results showed that SARA cows displayed high concentrations of ruminal volatile fatty acids, lactic acid and lipopolysaccharide (LPS). Furthermore, the blood concentrations of LPS and acute phase proteins ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 26 publications
(46 reference statements)
7
73
1
3
Order By: Relevance
“…Although plasma LPS was not measured in the current study, the upregulated TLR4 expression indicates the possibility that LPS was involved in the inflammatory response of OF-induced ARA. The presence of LPS in the blood has been shown in experimentally induced SARA (5)(6)(7). It has also been shown that plasma LPS was increased 8 h after OF overload and declined after 12 h in horses (23).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Although plasma LPS was not measured in the current study, the upregulated TLR4 expression indicates the possibility that LPS was involved in the inflammatory response of OF-induced ARA. The presence of LPS in the blood has been shown in experimentally induced SARA (5)(6)(7). It has also been shown that plasma LPS was increased 8 h after OF overload and declined after 12 h in horses (23).…”
Section: Discussionmentioning
confidence: 90%
“…In addition to lactate, lipopolysaccharide (LPS) has also been considered to be a major factor in the development of ruminal acidosis. LPS is generally assumed to be translocated into the blood stream during experimentally induced subacute ruminal acidosis (SARA) (5)(6)(7). These substances cause systemic inflammatory responses, but dynamic changes of innate immunity still remain unclear in ARA, particularly the role of polymorphonuclear neutrophil (PMN).…”
Section: Introductionmentioning
confidence: 99%
“…Rumen pH <6 for a prolonged period for several hours a day can adversely leads to acidosis, (Rodríguez‐Lecompte et al ). Recently, Zhao et al () indicated that SARA produces a high concentration of ruminal LPS, which over activates the inflammatory pathways and significantly increases the expression and synthesis of pro‐inflammatory cytokines in the rumen epithelium, thus causing partial inflammation of the rumen. Therefore, it is expedient to stabilize rumen pH and prevent it from reaching the acidosis state.…”
Section: Impact Of Feeding Single‐cell Fungi On Rumen Fermentation Acmentioning
confidence: 99%
“…Ruminal pH is also a crucial parameter to ensure the normal functioning of the rumen and its microbiome. Therefore, it is the closest and most accurate indicator of rumen health or disorders such as SARA, because it provides direct information about the conditions within the rumen (Enemark 2008 Zhao et al (2018) indicated that SARA produces a high concentration of ruminal LPS, which over activates the inflammatory pathways and significantly increases the expression and synthesis of pro-inflammatory cytokines in the rumen epithelium, thus causing partial inflammation of the rumen. Therefore, it is expedient to stabilize rumen pH and prevent it from reaching the acidosis state.…”
Section: Rumen Ph Acidosis and Its Implicationsmentioning
confidence: 99%
See 1 more Smart Citation